Die bronteksouteur se bydrae tot die produksieproses van literêre vertalings - Spies, Carla Marie (Stellenbosch Papers in Linguistics Plus, 2015)
OpsommingIn hierdie artikel word ŉ empiriese studie onderneem waarin die bydrae van die bronteksouteur in die produksieproses van literêre vertaling bestudeer word. Om hierdie doel te bereik, word drie produksieprosesse van literêre vertalings, To hell with Cronjé (Winterbach 2007b), My name is Vaselinetjie (Von Meck 2009a) en In bushveld and desert: A game ranger’s life (Bakkes 2008) retrospektiewelik bestudeer deur elke proses te herkonstrueer om die veranderinge wat die bronteksouteurs aangebring het, asook hulle korrespondensie met ander produksieagente, bloot te lê. Hiervoor word manuskripte, notas en e‑poskorrespondensie wat tydens elke produksieproses geproduseer is, kwalitatief ontleed. Antwoorde op semi‑gestruktureerde vraelyste word ook as sekondêre data bestudeer om die produksieagente die geleentheid te bied om oor die produksieproses te reflekteer en aan die navorser dinamika en aangeleenthede wat nie uit die primêre data afgelei kon word nie, te verduidelik. Die ontleding word gedoen teen die agtergrond van relevante sosiologiese, vertaal- en redigeer/revisieteorie, en bevindinge van vorige studies wat in die agtergrondbespreking aangebied word. Uit die analise kan daar gesien word dat alhoewel al die produksieagente ŉ beduidende rol in die produksie van ŉ literêre vertaling speel, wil dit wel voorkom of die bronteksouteur die produksieagent is wat die meeste status/outoriteit in die produksieproses geniet en gevolglik ook die meeste mag het en invloed kan uitoefen. Verder kan daar gesien word dat die betrokkenheid van die bronteksouteur in al drie prosesse voordelig was om inhoudelike foute en verkeerde interpretasies uit te skakel en ander produksieagente se vrae te beantwoord. Daar word egter ook aangedui dat die betrokkenheid van die bronteksouteur in sekere opsigte nadelig vir die produksieproses kan wees, byvoorbeeld wanneer hy/sy die teks tot só ŉ mate oorvertaal dat hy/sy as’t ware die rol van die vertaler oorneem en/of ander produksieagente ondermyn, wat wedywering en ŉ magswanbalans tot gevolg kan hê en die produksieproses kan strem.The source text author’s contribution to the production process of literary translationsExtended abstractDuring the production of a literary translation, a team of agents usually works very closely together to produce a target text. Therefore, the translation product cannot be attributed to the translator alone, as it is also influenced and shaped by other production agents.This article centres on the way in which the source text author, as a production agent, could contribute to the production process of literary translations. For this purpose, three literary works of prose translated by the South African literary translator, Elsa Silke, are analysed, namely To hell with Cronjé (Winterbach 2007b), My name is Vaselinetjie (Von Meck 2009a) and In bushveld and desert: A game ranger’s life (Bakkes 2008). The story in To hell with Cronjé takes place during the last weeks of the Anglo‑Boer War (South African War, 1899‑1902) and is about a group of Boer soldiers who help to bring a traumatised young man back to his parents’ home. The story centres on the experiences of two of these men, the two natural scientists, Reitz Steyn and Ben Maritz. My name is Vaselinetjie is about a white child, Helena Bosman, who was thrown away as a baby and raised by a coloured couple. She is removed from her home when she is 10 years old and taken away to a children’s home by welfare workers. There she is confronted by the “bad side” of society: drugs, gangs and cruel people. The novel tells the story of how she deals with and overcomes these circumstances. In bushveld and desert: A game rangers’ life is a collection of short stories, of an autobiographical nature, about Chris and his experiences as a game warden, wildlife expert, traveller and soldier in Africa.The production processes are analysed retrospectively by reconstructing them from manuscripts, notes and email correspondence produced during each process. This content analysis allows the researcher to observe the changes made to the translated texts by the source text authors and to reveal the extent and nature of these authors’ collaboration and correspondence with other production agents during the process. Answers to semi-structured questionnaires are also used as additional data to provide production agents’ reflections on the production processes and to explain aspects of the production process that are not clear from the data analysis. The production processes are analysed qualitatively and the results are presented against the backdrop of relevant sociological, translation and editing/revision theories, as well as previous studies on similar topics conducted in the field of translation studies.Subsequently, inferences are made regarding the position of the source text author within the production process, his/her power/authority within this process, his/her interaction with other production agents and the influence of his/her involvement on the production process and the target text.Based on the data analysis, it is determined that the source text authors were involved in the translation production process upon request by the publisher/commissioning editor and were given a large degree of freedom to be as involved in the production process as they wished to be. All three source text authors in this study were approached to answer other production agents’ questions and notes, and questions were often directed at them. The type of amendments they made, or aspects they commented on during their revision processes, typically regarded transfer and content, and to a lesser extent style and language usage (compare Mossop’s [2007] revision parameters). This was often done in collaboration with other production agents. The source text authors did not typically make amendments regarding structure and grammar. This was mainly done by the editors in the three processes analysed in this study. The translator also paid attention to these aspects. In the production processes of To hell with Cronjé and My name is Vaselinetjie the work that was performed by the source text authors could be seen as revision/editing as they worked through the entire text and made amendments to it. Furthermore, in To hell with Cronjé the source text author helped to translate and rewrite some sections. In My name is Vaselinetjie the source text author retranslated and rewrote or added text to a great extent. Both these source text authors also commented on the inputs of other production agents and answered their questions by means of emails and notes. They also posed questions to the other production agents. The source text author of In bushveld and desert: A game ranger’s life was not as actively involved in the production of the target text, but was consulted throughout for inputs and to answer other production agents’ questions and clarify meaning. Here and there, he rewrote small sections of the text and added some text where it was necessary to make the text more accessible to the target text reader. From the analyses, it could be seen that the source text author could be involved in the production process of literary translations in various capacities and to various extents.In general, based on the three production processes analysed, it seems that the source text author is the production agent who has the most status in the production process as well as the most power/authority. The source text authors’ power/authority within the production processes is illustrated by their influence on the selection of production agents, the publishers’ and commissioning editors’ respect for them and loyalty towards them by, for example, allowing them to have the last say in decisions that will influence the target text, and the fact that they were approached for advice and inputs throughout the processes.From the analyses, it could be seen that the involvement of the source text authors was advantageous in all three production processes to correct mistakes in the content, eliminate incorrect interpretations and to answer other production agents’ questions. In all three production processes analysed, the source text authors played an important role in this regard. This confirms the recommendation in Translation in practice (Paul 2009) that the source text author should ideally be involved in the production process of translations.It is also shown that the involvement of the source text author could be harmful to the process, for example when (s)he retranslates the text to such an extent that (s)he takes over the role of the translator or undermines other production agents, as happened in the production process of My name is Vaselinetjie. The publisher or commissioning editor could act as a social mediator by trying to resolve the power imbalance, rivalry/competition and conflict that could occur during the production process (compare Bogic 2009) to ensure that cooperation takes place in a productive manner.Therefore, it seems evident that the source text author should be careful not to retranslate or rewrite the translated text and, by doing that, take over the role of the translator and undermine his/her authority as the translation expert in the production process, and consequently cause power imbalances, rivalry/competition and conflict that strain the production process.The opportunity for self-translation can, however, be created within the production process of literary translations, where the source text author translates the entire text him/herself (“self‑translation”, compare Cordingley 2013). Consequently, an interesting follow-up study would be to see how the production processes of translations differ between where the source text author is also the translator of his/her own text versus where a translator translates a text. Another interesting study would be to compare translation processes where the source text author is involved versus where the source text author is not consulted at all during the production process.